Soluble guanylyl cyclase stimulation and phosphodiesterase‐5 inhibition improve portal hypertension and reduce liver fibrosis in bile duct–ligated rats. Issue 10 (12th January 2020) - Brusilovskaya, Ksenia; Königshofer, Philipp; Lampach, Daniel; Szodl, Adrian; Supper, Paul; Bauer, David; Beer, Andrea; Stift, Judith; Timelthaler, Gerald; Oberhuber, Georg; Podesser, Bruno Karl; Seif, Martha; et al.
Abstract : Background: In cirrhosis, the nitric oxide‐soluble guanylyl cyclase (sGC)‐cyclic guanosine monophosphate (cGMP) pathway is impaired, which contributes to increased intrahepatic vascular resistance (IHVR) and fibrogenesis. We investigated if sGC stimulation (riociguat (RIO)), sGC activation (cinaciguat (CINA)) or phosphodiesterase (PDE)‐5 inhibition (tadalafil (TADA)) improves portal hypertension (PHT) and liver fibrosis. Methods: Fifty male Sprague–Dawley rats underwent bile‐duct ligation (BDL) or sham operation. RIO (0.5 mg/kg), CINA (1 mg/kg), TADA (1.5 mg/kg) or vehicle (VEH) was administered from weeks 2 to 4 after BDL. At week 4, invasive haemodynamic measurements were performed, and liver fibrosis was assessed by histology (chromotrope‐aniline blue (CAB), Picro‐Sirius red (PSR)) and hepatic hydroxyproline content. Results: Cirrhotic bile duct–ligated rats presented with PHT (13.1 ± 1.0 mmHg) and increased IHVR (4.9 ± 0.5 mmHg⋅min/mL). Both RIO (10.0 ± 0.7 mmHg, p = 0.021) and TADA (10.3 ± 0.9 mmHg, p = 0.050) decreased portal pressure by reducing IHVR (RIO: –41%, p = 0.005; TADA: –21%, p = 0.199) while not impacting heart rate, mean arterial pressure and portosystemic shunting. Hepatic cGMP levels increased upon RIO (+239%, p = 0.006) and TADA (+32%, p = 0.073) therapy. In contrast, CINA dosed at 1 mg/kg caused weight loss, arterial hypotension and hyperlactataemia in bile duct–ligated rats. Liver fibrosis area was significantly decreased by RIO (CAB: –48%, p = 0.011; PSR: –27%, p = 0.121) and TADA (CAB: –21%, p = 0.342; PSR: –52%, p = 0.013) compared to VEH‐treated bile duct–ligated rats. Hepatic hydroxyproline content was reduced by RIO (from 503 ± 20 to 350 ± 30 µg/g, p = 0.003) and TADA (282 ± 50 µg/g, p = 0.003), in line with a reduction of the hepatic stellate cell activation markers smooth‐muscle actin and phosphorylated moesin. Liver transaminases decreased under RIO (AST: –36%; ALT: –32%) and TADA (AST: –24%; ALT: –27%) treatment. Hepatic interleukin 6 gene expression was reduced in the RIO group (–56%, p = 0.053). Conclusion: In a rodent model of biliary cirrhosis, the sGC stimulator RIO and the PDE‐5 inhibitor TADA improved PHT. The decrease of sinusoidal vascular resistance was paralleled by a reduction in liver fibrosis and hepatic inflammation, while systemic haemodynamics were not affected.